Perundungan Dalam Novel Kisah Untuk Geri Karya Erisca Febriani - Nurul Faizah Eka Putri Riziqni; Zulfadhli (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2023)
Bullying is a social phenomenon that still frequently occurs in school or community settings. Bullying is also considered a public issue that receives global attention, both domestically and internationally. One example is in the world of literature, such as in the novel